2021
DOI: 10.3389/fnagi.2021.755164
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Rho Kinase by Fasudil Ameliorates Cognition Impairment in APP/PS1 Transgenic Mice via Modulation of Gut Microbiota and Metabolites

Abstract: Background: Fasudil, a Rho kinase inhibitor, exerts therapeutic effects in a mouse model of Alzheimer's disease (AD), a chronic neurodegenerative disease with progressive loss of memory. However, the mechanisms remain unclear. In addition, the gut microbiota and its metabolites have been implicated in AD.Methods: We examined the effect of fasudil on learning and memory using the Morris water-maze (MWM) test in APPswe/PSEN1dE9 transgenic (APP/PS1) mice (8 months old) treated (i.p.) with fasudil (25 mg/kg/day; A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 80 publications
1
16
0
Order By: Relevance
“…Though data are still inconclusive, gut bacteria family and genus shifts might represent promising tools as novel biomarkers for the diagnosis and progression of AD, and the restoration of gut microbiota balance a potential therapeutic approach [ 380 ]. Several bacterial metabolites are already used as fecal biomarkers to characterize dysbiosis in AD patients; for instance, higher levels of trimethylamine N-oxide (a microbial metabolite implicated in immune response activation), enhanced oxidative stress, and intestinal barrier dysfunction have been identified in MCI and AD patients compared to cognitively unimpaired individuals [ 381 , 382 ].…”
Section: Resultsmentioning
confidence: 99%
“…Though data are still inconclusive, gut bacteria family and genus shifts might represent promising tools as novel biomarkers for the diagnosis and progression of AD, and the restoration of gut microbiota balance a potential therapeutic approach [ 380 ]. Several bacterial metabolites are already used as fecal biomarkers to characterize dysbiosis in AD patients; for instance, higher levels of trimethylamine N-oxide (a microbial metabolite implicated in immune response activation), enhanced oxidative stress, and intestinal barrier dysfunction have been identified in MCI and AD patients compared to cognitively unimpaired individuals [ 381 , 382 ].…”
Section: Resultsmentioning
confidence: 99%
“…Inhibition of RhoA/ROCK2/Limk1/cofilin signaling pathway rescued the memory impairments and synaptic disorder in AD rat (Han et al, 2020 ). ROCK inhibitors could also reduce synaptic damage and promote nerve regeneration in AD mice (Yan et al, 2021 ). Recent studies indicated that ROCK2 is a promising therapeutic target for AD (Cai et al, 2021 ; Weber & Herskowitz, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, although initially hypothesized for gastrointestinal disorders [ 102 ], gut microbiome-derived biomarkers have also been considered for psychological and neurodegenerative diseases (i.e., bipolar disorder, multiple Sclerosis, and PD), reporting powerful predictivity and differential diagnosis ability [ 103 , 104 , 105 ]. Regarding AD, promising results have recently been obtained, and Table 1 summarizes the main findings [ 72 , 73 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 ] ( Table 1 ). Whilst species of Prevotella and Helicobacter have been shown to be significantly different between APP/PS1 transgenic mice and controls, Actinobacteria and TM7 phylum seem to be more accurate in diagnosing AD when using the triple transgenic mouse model [ 106 , 107 , 109 ].…”
Section: Mainmentioning
confidence: 99%
“…Regarding AD, promising results have recently been obtained, and Table 1 summarizes the main findings [ 72 , 73 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 ] ( Table 1 ). Whilst species of Prevotella and Helicobacter have been shown to be significantly different between APP/PS1 transgenic mice and controls, Actinobacteria and TM7 phylum seem to be more accurate in diagnosing AD when using the triple transgenic mouse model [ 106 , 107 , 109 ]. Changes in beta diversity and variations in circulating metabolites involved in inflammatory pathways and metabolism of nucleotides, lipids, and sugars (i.e., glutamate, hypoxanthine, thymine, hexanoyl-CoA, and leukotrienes) have also been considered in the same studies, showing promising results [ 106 , 107 ].…”
Section: Mainmentioning
confidence: 99%
See 1 more Smart Citation